1998
DOI: 10.1111/j.1469-7793.1998.047bz.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of tyrosine phosphorylation in leptin activation of ATP‐sensitive K+ channels in the rat insulinoma cell line CRI‐G1

Abstract: Using whole‐cell and cell‐attached recording configurations, the role of phosphorylation in leptin activation of ATP‐sensitive K+ (KATP) channels was examined in the rat CRI‐G1 insulinoma cell line. Whole‐cell current clamp recordings demonstrated that, following dialysis with the non‐hydrolysable ATP analogue 5′‐adenylylimidodiphosphate (AMP‐PNP; 3‐5 mM), the leptin‐induced hyperpolarization and increase in K+ conductance were completely inhibited. Under current clamp conditions, application of the broad‐spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…These studies in human islets further add to a mounting body of evidence showing that leptin suppresses insulin secretion by pancreatic β-cells (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)32) and does so by activating the ATP-sensitive K + channel on β-cells (21,27,30). Further, these studies augment the available evidence that leptin inhibits not only insulin secretion, but also the expression of the proinsulin gene.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These studies in human islets further add to a mounting body of evidence showing that leptin suppresses insulin secretion by pancreatic β-cells (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)32) and does so by activating the ATP-sensitive K + channel on β-cells (21,27,30). Further, these studies augment the available evidence that leptin inhibits not only insulin secretion, but also the expression of the proinsulin gene.…”
Section: Discussionsupporting
confidence: 56%
“…Germane to the studies undertaken and described herein is that leptin also acts directly on receptors in pancreatic β-cells to suppress insulin secretion in rodents (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Leptin suppresses insulin secretion, insulin messenger ribonucleic acid (mRNA) levels, and transcription from the rat insulin promoter (30a) in isolated islets, perfused pancreata of mice and rats, and rats studied in vivo.…”
mentioning
confidence: 99%
“…Consequently, activation of K ATP channels in pancreatic ␤-cells by leptin reduces cytosolic calcium concentration, and this fall can be overcome by coincubation with 20 mmol/l glucose and GLP-1 (10 nmol/l). Although the molecular mechanism by which leptin activates K ATP channels is not fully understood, studies indicate that phosphorylation or dephosphorylation of proteins may be involved (51), and treatment of insulinoma HIT-T15 cells with murine leptin results in a threefold activation of phosphatidylinositol (PI) 3-kinase (21). Phosphodiesterase 3B, which reduces the cellular content of cAMP, is also activated by leptin, and leptin (1-5 nmol/l) suppressed the elevation of cAMP induced by GLP-1 in HIT-T15 cells (5 nmol/l) (21).…”
Section: Multiple Molecular Effects Of Leptin In Pancreatic ␤-Cellsmentioning
confidence: 99%
“…The different functional, molecular, and gene regulatory effects of leptin involving insulin secretion (8,18 -28, 30,31,33-40,42-44,51-61), pancreatic ␤-cell gene expression (19,20,31,38,62,63), and signal transduction (21,22,27,38,51,54,64) are summarized in Table 1.…”
Section: Multiple Molecular Effects Of Leptin In Pancreatic ␤-Cellsmentioning
confidence: 99%
“…Recently, it has been reported that stimulation of the mGluR 1 receptor produces the opening of a cationic channel directly by activation of Src-type of protein tyrosine kinase without activation of the trimeric G protein [37]. Furthermore, stimulation of a certain type of cytokine receptor family, such as leptin receptor, can activate a protein phosphatase to open the K ATP channel without the activation of trimeric G protein [38].…”
Section: Electrophysiological and Pharmacological Characteristics Of Kmentioning
confidence: 99%